Analysis of Cost Efficiency, Travel Time, Characteristics of Goods and Load Capacity on The Selection of Transportation Modes Through Route Optimization as a Mediating Variable - Christin M; Maniah Maniah; Erna Mulyati (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
The Influence of Cost Efficiency, Transit Time, Shipment Characteristics, and Load Capacity on Transportation Mode Selection through Route Optimization as a Mediating Variable at PT Pos Indonesia Regional III Bandung. The increasing complexity of logistics distribution and higher service demands require companies to improve transportation efficiency through effective management of cost efficiency, transit time, shipment characteristics, and load capacity. This study aims to analyze the influence of cost efficiency, transit time, shipment characteristics, and load capacity on transportation mode selection through route optimization as a mediating variable at PT Pos Indonesia Regional III Bandung. This research employed a quantitative approach using Structural Equation Modeling–Partial Least Squares analysis. Data were collected through questionnaires distributed to respondents involved in the company’s distribution and transportation activities. The results indicate that cost efficiency, transit time, shipment characteristics, and load capacity have a positive and significant effect on route optimization. Furthermore, route optimization has a positive and significant effect on transportation mode selection. Cost efficiency, transit time, shipment characteristics, and load capacity also positively influence transportation mode selection both directly and indirectly through route optimization. The study concludes that route optimization plays a crucial role in improving transportation mode selection decisions and enhancing distribution efficiency within the company.